2005
DOI: 10.1037/0021-9010.90.5.972
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuating Effect of Role Overload on Relationships Linking Self-Efficacy and Goal Level to Work Performance.

Abstract: The reported research examines the moderating effects of role overload on the antecedents and consequences of self-efficacy and personal goal level in a longitudinal study conducted in an industrial selling context. The results indicate that role overload moderates the antecedent effect of perceived organizational resources on self-efficacy beliefs. They also show that role overload moderates the direct effects of both self-efficacy and goal level on performance, such that these relationships are positive when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(161 citation statements)
references
References 20 publications
6
145
0
10
Order By: Relevance
“…Interestingly, the same section of the article did not offer a single caveat about advancing causal arguments on the basis of a nonexperimental study. Brown, Jones, and Leigh (2005). Using data from a nonexperimental study of representatives of an office supply manufacturer, the authors tested an assumed causal model in which self-efficacy was viewed as a mediator of relations between (a) the assumed antecedents of previous performance and organizational resources, and (b) the hypothesized consequence of current performance.…”
Section: The Relative Validity Of Inferences About Mediation In Recenmentioning
confidence: 99%
“…Interestingly, the same section of the article did not offer a single caveat about advancing causal arguments on the basis of a nonexperimental study. Brown, Jones, and Leigh (2005). Using data from a nonexperimental study of representatives of an office supply manufacturer, the authors tested an assumed causal model in which self-efficacy was viewed as a mediator of relations between (a) the assumed antecedents of previous performance and organizational resources, and (b) the hypothesized consequence of current performance.…”
Section: The Relative Validity Of Inferences About Mediation In Recenmentioning
confidence: 99%
“…With regard to the latter, Brown, Jones, and Leigh (2005) found that role overload (excess work without the necessary resources to accomplish a task) moderates goal effects; goals affected performance only when overload was low.…”
mentioning
confidence: 99%
“…Finally, situational constraints such as role overload can affect goal setting. When role overload is high, goals are less likely to affect performance (Brown, Jones, & Leigh, 2005). In addition to these four conditions under which goal setting is less effective, we suggest goal targets can be ''miscalibrated,'' or inappropriately set in predictable ways, which can lead to unexpected negative consequences.…”
Section: Part B: Goal Targetsmentioning
confidence: 99%